O SUAS e o Projeto Ético Político dos Assistentes Sociais: uma análise a partir dos assistentes sociais do município de Formiga-MG - Souza, Jaqueline Aparecida [UNESP] (2014)
The Politics of Social Welfare , the promulgation of the Federal Constitution of 1988, receives the status of public policy , citizen's right and duty of the State to be provided to those who need it (in theory) . Subsequent enactment of the Magna Carta have the approval of the Organic Law of Social Assistance (Law 8.742/93) recently amended by Law 12.435/11 , National Social Assistance Policy (PNAS 2004) and Unified Social Assistance (SUAS, 2005). These regulations that advance the consolidation of the Brazilian protective system, materializing multiple workspaces ordering the presence of several professionals, including social workers. Given this, the objective is to understand how social workers, of Formiga/MG understand and conduct professional work spaces in consolidated social assistance from the adoption of its , prioritizing this study the level of basic social protection. It is emphasized further in this work, the need to articulate the precepts of Political Ethics Project as a guiding component of professional practice under the Social Assistance Policy. For the realization of this research five social workers were interviewed , four of which work on Basic Social Protection , and one in Special Social Protection of the its. It was evidenced by the completion of this study that there are tensions between the principles of Ethical Political Project of Social Workers and the principles of social assistance policy, as established by the major normative. This is demonstrated through theoretical and empirical study. Moreover, it became clear how this policy is being implemented in Ant and the main difficulties raised by professionals to implement the same in this city